Research on Strategic Communication Analysis of Interpersonal Communication - Shen, Hua; Ma, Tianchen (Advances in Social Sciences Research Journal, 2020)
In this paper, we have discussed interpersonal communication. Basically, communication is strategic when behaviors (utterances, nonverbal displays) are formulated in a particular way because it is projected that they will have social utility. And Strategic interpersonal communication assumes certain characteristics that are common to behavior. As Communication is a vehicle that organizations should use to initiate, develop, maintain, and repair mutually productive organization- public relationships. We discusses many aspects of Strategic Interpersonal Communication such as its multi-dimensions, Relationship negotiation and Interpersonal Communication and Public Relations. In methodology section we have carried out study. This study was intended to recognize and measure the perceptions of sophomore and junior semester college students toward feelings of anxiety experienced throughout foreign language learning as measured by the FLCAS scale. This study results that anxiety in foreign language university students by diminishing their indifference and disinterest in the curriculum that is distinct to their needs, educators have to give meaningful content that is similar to their particular disciplines. An instance of this approach would be to expand curricula for professional disciplines, such as health career, business, science and technology, and law, and diversely curricula for educational purposes, for example, for students majoring in the language or for those practicing their undergraduate or postgraduate studies out of the country.